Prevalence, pattern and determinants of disabilities in India: Insights from NFHS-5 (2019–21) - Sweta Pattnaik; Jogesh Murmu; Ritik Agrawal; Tanveer Rehman; Srikanta Kanungo; Sanghamitra Pati (Frontiers in Public Health, 2023)
There is a need to provide an overview of the disability burden in India as there are limited studies. The present study aimed to estimate the prevalence and assess the pattern and determinants of disability in India. We analyzed National Family Health Survey-5 data using the “svyset” command in STATA software. We assessed the correlates by multivariable regression and reported an adjusted prevalence ratio (aPR) with a 95% confidence interval (CI). QGIS 3.2.1 software was used for spatial analysis of distributions of different disabilities. The mean (SD) age of 28,43,917 respondents was 30.82 (20.62) years, with 75.83% (n = 21,56,633) and 44.44% (n = 12,63,086) of them being from a rural area and were not educated, respectively. The overall prevalence of disability was 0.93% [(95% CI: 0.92–0.95), n = 26,435] and 5.11% of households have one or more people with disability (PwD). Locomotor disabilities accounted for 44.73% of all disabilities (n = 10,730), followed by mental disabilities (20.07%, n = 4,814). Age 75 years and above (vs. 0–14 years) [aPR: 26.35 (23.63–29.37)], male (vs. female) [aPR: 1.58 (1.52–1.64)], no education (vs. higher education) [aPR: 4.42 (4–4.87)], unmarried (vs. married) [aPR: 8.85 (8.27–9.47)], seeking care of non-governmental organization (NGO) (vs. other) [aPR: 1.34 (0.95–1.89)] were significant independent determinants. The highest overall prevalence of disability and locomotor was in Lakshadweep/UTs (1.68%) and Delhi (58.5%), respectively. Out of every hundred individuals in India, one has a disability, and five out of every hundred households have one or more people with a disability. More intervention strategies should be planned, considering factors like education, residence, health promotion and caste so that the services provided by the government can be available and accessible to everyone in need.